2010
DOI: 10.3201/eid1605.091427
|View full text |Cite
|
Sign up to set email alerts
|

Historical Distribution and Molecular Diversity ofBacillus anthracis, Kazakhstan

Abstract: This study provides useful baseline data for guiding future disease control programs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
47
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(52 citation statements)
references
References 17 publications
(43 reference statements)
5
47
0
Order By: Relevance
“…A total of 487 outbreaks from 1932 and 2006 were captured by the Nidus database (Table 2). Domestic cattle and sheep made up 56.3% and 21.6%, respectively, with horses, swine, unknown (unrecorded) species, donkeys, polecats (from fur farming operation 6 ) and animal hides composing the remainder of the outbreaks. Outbreaks per month are illustrated in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
See 4 more Smart Citations
“…A total of 487 outbreaks from 1932 and 2006 were captured by the Nidus database (Table 2). Domestic cattle and sheep made up 56.3% and 21.6%, respectively, with horses, swine, unknown (unrecorded) species, donkeys, polecats (from fur farming operation 6 ) and animal hides composing the remainder of the outbreaks. Outbreaks per month are illustrated in Figure 3.…”
Section: Resultsmentioning
confidence: 99%
“…In contrast, neighboring Kazakhstan reported more sheep outbreaks compared with cattle during a similar reporting period . 6 Although differences may be due to variation in susceptibility or their geographic distribution, it has been suggested that as cattle are more valuable, sheep losses from anthrax may go undetected if outbreaks are small. 5 Interestingly, sheep herding practices tend to include highaltitude summer pastures, 29 which may reduce exposure to B. anthracis during summer months (based on our ENM predictions; Figure 4); though exposure to mid-elevation grasses could result in exposure during the migration up to or down from summer grazing.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations